Assessing the role of medical entomology in general medicine education in Iran: expert perspectives and curriculum implications - Abbasi, Ebrahim; Bazrafkan, Lila; Faghihi, Seyed Ali Akbar; Azizi, Kourosh; Moemenbellah-Fard, Mohammad Djaefar (BMC medical education, 2025)
The Ministry of Health, Treatment and Medical Education in Iran has tried integrating the primary science curriculum with the clinical program. This means educational reform has been implemented in most medical schools in Iran. In the study of the medical entomology Discipline, prioritization of educational needs, and determination of appropriate solutions to improve the status of the entomology Discipline in the Faculty of Medicine and Health, the basis of experts' opinions were examined and analyzed. Insert the subject of medical entomology into the Medicine Discipline at the Faculty of Medicine and Health. The Nominal Group Technique (NGT), which was the papers for recording the opinions of the professors, was done after the focus group. In the focus group, the professors discussed the results obtained from the NGT. This method used the Delphi technique to exchange opinions (disagreement and consensus of experts). According to the findings of this study, after two technical sessions of the Nominal group, the weak and strong points and required subjects for revision of the chapters of the medical entomology curriculum were determined. Medical entomology in Iranian universities of medical sciences is one of the important topics of medical parasitology Disciplines for general medical students because it provides information about Disease-vector insects and ways to control them (Results two rounds of Delphi). The educational program of the entomology Discipline needs to be revised and evaluated after the implementation of the revised program.